Pengaruh implementasi UU No. 8 Tahun 1999 tentang Perlindungan Konsumen terhadap perilaku doom spending mahasiswa - Nuria, Wafiq Sinta (Maliki Interdisciplinary Journal, 2024)
This study aims to analyze the impact of the implementation of Law No. 8 of 1999 on Consumer Protection on doom spending behavior among university students. Doom spending refers to excessive and uncontrolled consumption behaviors, often driven by social pressures, economic conditions, or lack of understanding of consumer rights. The implementation of the Consumer Protection Law is expected to provide better awareness of consumer rights and obligations, protecting them from harmful business practices. The study uses a survey method with a sample of students from several universities in Indonesia. The results indicate that understanding of the Consumer Protection Law has a significant impact on controlling consumptive behaviors, although other factors such as peer influence and advertising also play important roles. Overall, consumer rights education can reduce doom spending behavior and encourage more rational consumption patterns among students.